Severe bony ankylosis of the temporomandibular joint on one side and contralateral adhesion: A case report - Song, Ji-Young (Imaging Sci Dent, 2015)
Bony fusion between the mandibular condyle and skull base involves temporomandibular joint (TMJ) bony ankylosis. This condition might originate from trauma, infection, or systemic disease. TMJ adhesion can develop after synovial damage. Both TMJ ankylosis and adhesion lead to functional impairment and pain. Here, we present a case of a 50-year-old female who had bony ankylosis of the right TMJ and adhesion of the left TMJ. She had otitis media in the right ear. A large mass in the right TMJ was observed on computed tomograph. Magnetic resonance image showed a large fused bone mass with normal bone marrow in the right TMJ and flattening of the condyle with a thin disk in the left TMJ. Gap arthroplasty with temporal fascia was performed on the right TMJ, and discectomy, high condylectomy, and coronoidectomy were performed on the left TMJ. During a 2-year follow-up after surgery, the patient had no recurrence.